2021
DOI: 10.1016/j.socscimed.2021.114039
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of older Swiss adults to the COVID-19 pandemic: A longitudinal survey on the acceptance of and adherence to public health measures

Abstract: Rationale An important public health strategy during the COVID-19 pandemic was the protection of people at risk of severe progressions of an infection; namely, older people and people with pre-existing conditions. Objective To improve public health communication, it is vital to understand, which sociodemographic and psychological factors drive older people’s acceptance of and compliance with public health measures. Method This goal was pursue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
4
21
2
2
Order By: Relevance
“…Indeed, our results indicate that trust in a government's ability to manage the pandemic was strongly related to the motivation to comply, considerably stronger than LC or DC. However, contrary to previous studies showing that trust in government is directly related to adherence ( Bearth et al, 2021 ; Pak et al, 2021 ; Uddin et al, 2021 ), we found no such a direct relationship. Instead, while LC and DC show stronger direct relations with self-reported adherence, trust in government appears to be potentially a key factor in enhancing an individuals' motivation to comply, but not – at least not directly – the actual adherence.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Indeed, our results indicate that trust in a government's ability to manage the pandemic was strongly related to the motivation to comply, considerably stronger than LC or DC. However, contrary to previous studies showing that trust in government is directly related to adherence ( Bearth et al, 2021 ; Pak et al, 2021 ; Uddin et al, 2021 ), we found no such a direct relationship. Instead, while LC and DC show stronger direct relations with self-reported adherence, trust in government appears to be potentially a key factor in enhancing an individuals' motivation to comply, but not – at least not directly – the actual adherence.…”
Section: Discussioncontrasting
confidence: 99%
“… Pak et al (2021) found that the importance of trust increases with the measures' stringency: the more restrictive the regulations, the more trust relates with adherence. Likewise, Bearth et al (2021) observed that individuals scoring high in trust in government were also more accepting of containment measures and reported more compliance. The finding was further corroborated among young individuals for whom lower trust in government was related to reduced willingness to adhere to distancing measures ( Nivette et al, 2021 ).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Perceived certainty of scientific evidence was measured with the objective sub-scale of Retzbach, Otto (22) with a good Cronbach’s alpha of α = .79. Both the scales for pandemic health fears (α = .92) and pandemic societal fears (α = .81) were taken from studies conducted in Switzerland during the SARS-CoV-2 pandemic in 2020 [ 25 , 26 ]. Two types of subjective knowledge were assessed by asking “What do you think: How much do you know about a) vaccines in general and b) mRNA vaccines against the corona virus (SARS-CoV-2)” with the response options 1: “little knowledge” to 7: “a great deal of knowledge.”…”
Section: Methodsmentioning
confidence: 99%